Training and Assistance in Publication of Scientific Articles of Research Results for Improving Teacher Professional Competence in Boalemo Regency: Pelatihan dan Pendampingan Publikasi Artikel Ilmiah Hasil Penelitian Untuk Peningkatan Kompetensi Profesionalisme Guru di Kabupaten Boalemo - Yusuf, Frida Maryati; Mardin, Herinda; Latjompoh, Masra (Yayasan Ahmar Cendekia Indonesia, 2023)
Writing and publishing scientific articles is a must in increasing professional competence for teachers. Various efforts have been made so that teachers have the ability to write and publish scientific articles resulting from research that has been carried out. One of the efforts is by training and assisting the publication of scientific research articles for teachers. The training and assistance for the publication of scientific articles resulting from research for teachers was carried out at Madrasah Tsanawiyah Negeri 2 Boalemo, Gorontalo Province. The method used in this activity is the Participant Active Learning method (Participants actively participate in conducting training and mentoring during the activity) and the training, mentoring and technical guidance approach (BIMTEK). Training and assistance in publishing scientific articles for teachers in Madrasah Tsanawiyah Negeri 2 Boalemo, Boalemo Regency, Gorontalo Province, is able to increase insight and knowledge as well as teacher professionalism competence in publishing scientific articles with direct learning and practical experience. This of course has a very positive impact on the progress of education and the improvement of teacher professional competence. Abstrak Menulis dan mempublikasikan artikel ilmiah merupakan suatu keharusan dalam meningkatkan kompetensi profesionalisme bagi guru. Beragam upaya yang dilakukan agar guru memiliki kemampuan dalam menulis dan publikasi artikel ilmiah hasil penelitian yang telah dilaksanakan. Salah satu upaya dengan pelatihan dan pendampingan publikasi artikel ilmiah hasil penelitian bagi guru-guru. Pelatihan dan pendampingan publikasi artikel ilmiah hasil penelitian bagi guru-guru ini dilaksanakan di Madrasah Tsanawiyah Negeri 2 Boalemo Provinsi Gorontalo. Metode yang dilakukan dalam kegiatan ini adalah metode Participant Active Learning (Peserta berpartisipasi aktif dalam melakukan pelatihan dan pendampingan selama kegiatan berlangsung) dan pendekatan pelatihan, pendampingan serta bimbingan teknis (BIMTEK). Pelatihan dan pendampingan publikasi artikel ilmiah bagi guru-guru di lingkungan Madrasah Tsanawiyah Negeri 2 Boalemo Kabupaten Boalemo, Provinsi Gorontalo mampu meningkatkan wawasan dan pengetahuan serta kompetensi profesionalisme guru dalam melakukan publikasi artikel ilmiah dengan pengalaman belajar dan praktek langsung. Hal ini tentu saja berdampak sangat positif bagi kemajuan pendidikan dan peningkatan kompetensi profesionalisme guru.